Apicultural characterization and sensory analysis of honeys from the Department of Nariño - Reina-López, Alejandra Mayeli; Sabogal-Aguilar, Juliana; Betancourth-Jurado, Andrés (Revista de Ciencias Agrícolas, 2026)
In Colombia, the beekeeping sector contributes to the strengthening of the rural economy and promotes the conservation of various strategic ecosystems. For this reason, this study aimed to identify the emergence of beekeeping, characterize beekeepers, and determine the sensory characteristics of honey in the Department of Nariño. Semi-structured interviews were conducted with long-standing beekeepers to identify the origins of beekeeping. Surveys were administered to producers from three identified beekeeping associations. For sensory analysis, honey samples were collected from three geographical zones to identify organoleptic characteristics specific to each area through a sensory panel. The results were analyzed using Multiple Correspondence Analysis (MCA). The results indicate that beekeeping in Nariño is highly heterogeneous and that the strengthening of bee farming originated from the capture of swarms, a product of Africanization. In the characterization of beekeepers, five factors were obtained that explain 44.22% of the variability in beekeeping production in the region; the factor with the greatest variability is related to the size of the productive unit. Regarding the sensory assessment of honey, descriptors for differentiating honey by geographical area were identified. In the sensory evaluation, mild aromas were found in the north, intense sweet and resinous profiles in the center, and complex aromas in the south. Multivariate analysis confirmed consistent groupings between areas, which supports the use of sensory attributes as tools for differentiating honeys and contributes to strengthening the regional beekeeping sector.